Defining the stimulus—A memoir - Terrace, Herbert (Behavioural processes, 2010)
The eminent psychophysicist, S.S. Stevens, once remarked that, “the basic problem of psychology was the definition of the stimulus” ( Stevens, 1951, p. 46). By expanding the traditional definition of the stimulus, the study of animal learning has metamorphosed into animal cognition. The main impetus for that change was the recognition that it is often necessary to postulate a representation between the traditional S and R of learning theory. Representations allow a subject to represent a stimulus it learned previously that is currently absent. Thus, in delayed matching-to-sample, one has to assume that a subject responds to a representation of the sample during test if it responds correctly. Other examples, to name but a few, include concept formation, spatial memory, serial memory, learning a numerical rule, imitation and metacognition. Whereas a representation used to be regarded as a mentalistic phenomenon that was unworthy of scientific inquiry, it can now be operationally defined. To accommodate representations, the traditional discriminative stimulus has to be expanded to allow for the role of representations. The resulting composite can account for a significantly larger portion of the variance of performance measures than the exteroceptive stimulus could by itself.